2005
DOI: 10.1016/j.jbankfin.2004.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Commitment or entrenchment?: Controlling shareholders and board composition

Abstract: This paper examines the determinants of board composition and firm valuation as a function of board composition in Taiwan -a country that features relatively weak protection for investors, firms with controlling shareholders, and pyramidal groups. The results suggest that there is poor governance when the board is dominated by members who are affiliated with the controlling family but good governance when the board is dominated by members who are not affiliated with the controlling family. In particular board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
220
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(243 citation statements)
references
References 41 publications
(79 reference statements)
20
220
2
1
Order By: Relevance
“…Greene, 2008, Chapter 3 effect of ownership identity and board attributes on a firm's revealed strategy choices, and (4) the consequences of these choices for firm financial performance (see Figure 1). Firm size was included to capture size-related board attribute contingency effects (Linck, Netter, & Yang, 2008;Yeh & Woidtke, 2005). All variables are described in Table 2.…”
Section: Masem Proceduresmentioning
confidence: 99%
“…Greene, 2008, Chapter 3 effect of ownership identity and board attributes on a firm's revealed strategy choices, and (4) the consequences of these choices for firm financial performance (see Figure 1). Firm size was included to capture size-related board attribute contingency effects (Linck, Netter, & Yang, 2008;Yeh & Woidtke, 2005). All variables are described in Table 2.…”
Section: Masem Proceduresmentioning
confidence: 99%
“…Further, the independence of non-executives could be weakened if they are appointed by a CEO or previous members of the firm management team [14,20]. 4 Moreover, [21] argued that insiders may provide a beneficial monitoring function since they may better understand the social and political aspects of a firm that are useful for compensation advisors in regard to structuring incentives. Congruent with their argument, [21] found that an increase in board independence has little impact on pay levels.…”
Section: Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
“…This led to the recent regulatory and policy reforms. 4 However, this position does not necessarily imply an association between affiliated or interdependent RC members and CEO compensation [11,15]. One possible reason for this is that affiliated or interdependent directors serving on a powerful committee are mindful of their duty to shareholders, regardless of their level of dependence [11].…”
Section: H1: Top Executive Compensation Levels Will Be Relatively Higmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies in the high-IS range sorted between 65% and 82% of companies over the sample period, and 71% of the companies belonged to the high-IS range. Yeh and Woidtke (2005) found that ultimate controllers in Taiwan had authority to choose both supervisors and directors, and could reinforce their power by choosing trusted people or family members. Boards of directors and supervisors in Taiwan are controlled by ultimate controllers associated to family conglomerates holding a huge part of equity, and usually have an motivation to join outside stockholder interests by contributing to the company's value (Villalonga and Amit, 2006;Maury, 2006).…”
Section: 1371mentioning
confidence: 99%